The Usage degree of Electronic Leadership by School Principals of Al- Baha city and its Relation to their Performance - Alghamdi, Saad Mesfer Safar; Almanie, Abdullah Mohammed Abdullah (Journal of Educational and Psychological Sciences, 2021)
The study aims at revealing the degree to which the leaders of the students’ schools in the e-administration in Al-Baha city from the teachers’ point of view used the descriptive approach in (1439-1440) the first term , and the study sample consisted of (250) teachers who applied to them his degree in the first semester of (27) paragraphs distributed in three fields, and the results showed that the degree to which the leaders of the city of Al-Baha used e-administration From the teachers’ point of view, the average computation was (3.16) by (63%) and the area of follow-up and e-evaluation was the first with an average of (3.34) and (66.8%). This is followed by an electronic steering and driving field with an average of (3.28) and (65.6%). The third and last order included the field of planning and electronic organization with an average of (2.90) and (58%). The results also showed that there are no statistically significant differences in the degree to which school leaders use e-management from the teachers’ point of view, which is attributed to the changing of the scientific qualification, experience, or educational stage, and the study recommended the necessity of improving the abilities of school leaders to use e-management and holding courses to activate e-management for the whole School system.